„To Believe” According to Edith Stein - Loba, Mirosław (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
The author begins with noticing an apparent absence of the problem of faith in the twentieth-century philosophy and its surprising return at the end of this century, notably in Gianni Vattimo’s and Julia Kristeva’s works. By creating a kind of dialogue between Stein’s phenomenology and Kristeva’s psychoanalysis, the author analyses the concept of faith from those two apparently distinct perspectives. In the discussion of Stein’s attitude recalledare her personal experiences as a philosopher along with her claims on faith as a foundation of knowledge of God, supplied by love and acting. From Kristeva’s point of view, far from the former one, the need of faith is a result of specific ‘going beyond oneself’ that is necessary in a process of forming one’s personal identity. While Stein believes in God, Kristeva believes in man.